Phenotypic integration in feliform carnivores: Covariation patterns and disparity in hypercarnivores versus generalists. (6th November 2020) - Michaud, Margot; Veron, Géraldine; Fabre, Anne‐Claire
Abstract: The skeleton is a complex arrangement of anatomical structures that covary to various degrees depending on both intrinsic and extrinsic factors. Among the Feliformia, many species are characterized by predator lifestyles providing a unique opportunity to investigate the impact of highly specialized hypercarnivorous diet on phenotypic integration and shape diversity. To do so, we compared the shape of the skull, mandible, humerus, and femur of species in relation to their feeding strategies (hypercarnivorous vs. generalist species) and prey preference (predators of small vs. large prey) using three‐dimensional geometric morphometric techniques. Our results highlight different degrees of morphological integration in the Feliformia depending on the functional implication of the anatomical structure, with an overall higher covariation of structures in hypercarnivorous species. The skull and the forelimb are not integrated in generalist species, whereas they are integrated in hypercarnivores. These results can potentially be explained by the different feeding strategies of these species. Contrary to our expectations, hypercarnivores display a higher disparity for the skull than generalist species. This is probably due to the fact that a specialization toward high‐meat diet could be achieved through various phenotypes. Finally, humeri and femora display shape variations depending on relative prey size preference. Large species feeding on large prey tend to have robust long bones due to higher biomechanical constraints.